The Effect of Wall Type and Environmental Conditions toward Blood Type Identification Success Rate in Identifying Criminal Evident - Dinar Putri Rahayu; Desti Christian Cahyaningrum; Bowo Nurcahyo (Jurnal Biologi Tropis, 2021)
Findings of blood at the crime scene (TKP) can provide important information in criminal cases such as homicide. Blood findings at crime scenes are usually blood spots or traces of blood that can be found on various substrates. This study aims to determine the type of wall substrate and environmental conditions that have the ability to preserve blood better, prove by success rate in identifying blood type in ABO system until 336 hour of exposure. In this study, blood samples were exposed to three variations of wall substrates, namely plastered walls, plastered and painted walls, plastered and oil-painted walls; and in two different environmental conditions (indoor and outdoor). The method used to identify blood type in this study was absorption elution. First, blood samples from substrate was transferred to a gauze by NaCl 0,98%. Then a confirmation test was carried out to ensure that the gauze sample contains a blood sample. Positive results of the confirmation test were indicated by a change in the color of the sample to bluish green when it is dripped with H2O2 and Leuco Malachite Green (LMG). The positive sample was then dripped with antiserum to determine the blood type. The success of identification of blood groups was indicated by the agglutination in the samples that were dripped with antisera A, because the blood samples used in this study are group A. The results showed that the success rate of blood group identification on the three types of substrates in the indoor environment for 336 hours was 100%. Meanwhile, in the outdoor environment, only blood samples exposed to plastered wall substrate and wall paint for 264 hours could be identified for their blood type. It can be concluded that the three types of wall substrates have the same ability to preserve blood samples for up to 336 hours of exposure, but the environmental conditions that give the best percentage of successful blood group identification were in indoor conditions. For further research is recommended to focus on external environmental factors that have the most influence on the success of blood group identification in dried blood samples.